La obra del padre Sobreira, fuente de la epigrafía medieval - Fernández García, Patricio M. (Estudios humanísticos. Geografía, historia y arte, 2001)
This paper is a first study of the manuscript of the XVIII century, whose autor is Juan Sobreira, like a indispensable source for the medieval Epigraphy. The raw material for this study has not been sufficiently available until now. This manuscript is very important because the author did a facsimile reproduction of each inscription. Here we do a comparative study to value the importance of this unpublished manuscript.